Pengaruh Electronic Word Of Mouth (Ewom) Terhadap Keputusan Pembelian Pada Shopee Dimediasi Oleh Citra Merek (Studi Kasus Mahasiswa FEB Unisma Angkatan 2019) - Mia Angellina; N Rachma; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study analyze the impact of Electronic Word of Mouth (Ewom) of Purchase Decisions on Shopee Mediated by Brand Image. The samples obtained were 100 respondents. The data was obtained from questions distributed to students of the Faculty of Economics and Business Class of 2019 at the Islamic University of Malang who had purchased at Shopee and chosen through purposive sampling. Data analysis in this study used SPSS version 25. Data analysis methods used in this study included validity testing, reliability testing, normality testing, path analysis, and research hypothesis testing. This study showed that the Electronic Word of Mouth directly influences brand image, the Electronic Word of Mouth does not influence Purchase Decisions, the Brand Image does not influence Purchase Decisions and Brand Image cannot mediate Electronic Word of Mouth on Purchase Decisions. Keywords: Electronic Word of Mouth, Brand image, Purchase Decision